Some properties of K-Operator Frame in Hilbert C^*-modules - Roumaissae Eljazzar; Mohamed Rossafi; Mohammed Klilou (Department of Mathematics, Hasanuddin University, 2022)
In this paper, we present some properties of K-operator Frame in Hilbert C^*-modules.Topics that will be discussed include: K-operator Frame and Dual K-operator frame in Hilbert C^*-modules.We will also study K-operator Frame in two Hilbert C^*-modules with different C^*-algebras.